2021
DOI: 10.3389/fimmu.2021.648945
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesviruses 6A and 6B in Reproductive Diseases

Abstract: Human herpesviruses 6A (HHV-6A) and human herpesvirus 6B (HHV-6B)—collectively, HHV-6A/B—are recently-discovered but ancient human viruses. The vast majority of people acquire one or both viruses, typically very early in life, producing an ineradicable lifelong infection. The viruses have been linked to several neurological, pulmonary and hematological diseases. In early human history, the viruses on multiple occasions infected a germ cell, and integrated their DNA into a human chromosome. As a result, about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
1
8
0
2
Order By: Relevance
“…With advances in next-generation sequencing technology, the characterization of the in utero microbiome is becoming increasingly clear. Although the biomass of microorganisms in the uterus is low (90-92), bacteria, viruses (such as adeno-associated virus, human herpes viruses and human cytomegalovirus) (93)(94)(95), Chlamydia (Chlamydia trachomatis) (96,97), Mycoplasma (Mycoplasma hominis) (98) and fungus (Candida albicans) (99) have been detected. In 2015, Mitchell et al (91) evaluated the endometrial flora of 58 patients by quantitative PCR, among which L. iners, Prevotella and L. crispatus were the most common.…”
Section: Vaginal Microbes In Gynecological Malignanciesmentioning
confidence: 99%
“…With advances in next-generation sequencing technology, the characterization of the in utero microbiome is becoming increasingly clear. Although the biomass of microorganisms in the uterus is low (90-92), bacteria, viruses (such as adeno-associated virus, human herpes viruses and human cytomegalovirus) (93)(94)(95), Chlamydia (Chlamydia trachomatis) (96,97), Mycoplasma (Mycoplasma hominis) (98) and fungus (Candida albicans) (99) have been detected. In 2015, Mitchell et al (91) evaluated the endometrial flora of 58 patients by quantitative PCR, among which L. iners, Prevotella and L. crispatus were the most common.…”
Section: Vaginal Microbes In Gynecological Malignanciesmentioning
confidence: 99%
“…11 Overall, HHV-6 transplacental infection occurs in 1%-2% of pregnancies and may play a role in 43% of cases of primary unexplained infertility. 12 Our findings suggest that when occurring in pregnant women, PR may herald a possible HHV-6 fetal infection, premature delivery, small for gestational age newborns and, under certain conditions, even fetal death.…”
Section: Pityriasis Rosea Human Herpesvirus 6 Infection and Pregnancymentioning
confidence: 63%
“…Its role during placentation is supported by the highest KIR2DL4 gene expression in healthy pregnant women compared to patients with recurrent spontaneous miscarriage [179]. In IUGR placentas, HHV-6 infection has been reported together with increased HLA-G expression which possibly affect dNK cell function engaging KIR2DL4 (Table 2) [121,123]. It was suggested that this effect on HLA-G expression and might be due the expression the U94 viral protein [122] (Figure 7).…”
Section: Herpesvirusesmentioning
confidence: 97%
“…Human Herpes Virus-6 (HHV-6) susceptibility association to peculiar KIR\HLA-I expression has been widely described. HHV-6 has been recently distinguished in two different viruses, HHV-6A and -6B, characterized by different biological features [123]. In particular, while HHV-6B tropism is more aimed at T cells, HHV-6A is able to infect a wide range of tissues and differently affects NK cell activation.…”
Section: Herpesvirusesmentioning
confidence: 99%